The Dynamics of Adult Basic Education Instruction - Hal Beder; Patsy Medina (Adult Education Research Conference, 1999)
This presentation reports the results of a classroom dynamics study of adult literacy education in which twenty adult literacy classes were observed twice in seven states. For each observed class, teachers were interviewed. Students were interviewed when possible. The overriding theme was classroom culture, defined as the socially patterned human thought and behavior that takes place in adult literacy education classrooms.